Differential alteration of fMRI signal variability in the ascending trigeminal somatosensory and pain modulatory pathways in migraine - Lim, Manyoel; Jassar, Hassan; Kim, Dajung J.; Nascimento, Thiago D.; DaSilva, Alexandre F. (Journal of headache and pain, 2021)
Background The moment-to-moment variability of resting-state brain activity has been suggested to play an active role in chronic pain. Here, we investigated the regional blood-oxygen-level-dependent signal variability (BOLD SV ) and inter-regional dynamic functional connectivity (dFC) in the interictal phase of migraine and its relationship with the attack severity. Methods We acquired resting-state functional magnetic resonance imaging from 20 migraine patients and 26 healthy controls (HC). We calculated the standard deviation (SD) of the BOLD time-series at each voxel as a measure of the BOLD signal variability (BOLD SV ) and performed a whole-brain voxel-wise group comparison. The brain regions showing significant group differences in BOLD SV were used to define the regions of interest (ROIs). The SD and mean of the dynamic conditional correlation between those ROIs were calculated to measure the variability and strength of the dFC. Furthermore, patients’ experimental pain thresholds and headache pain area/intensity levels during the migraine ictal-phase were assessed for clinical correlations. Results We found that migraineurs, compared to HCs, displayed greater BOLD SV in the ascending trigeminal spinal-thalamo-cortical pathways, including the spinal trigeminal nucleus, pulvinar/ventral posteromedial (VPM) nuclei of the thalamus, primary somatosensory cortex (S1), and posterior insula. Conversely, migraine patients exhibited lower BOLD SV in the top-down modulatory pathways, including the dorsolateral prefrontal (dlPFC) and inferior parietal (IPC) cortices compared to HCs. Importantly, abnormal interictal BOLD SV in the ascending trigeminal spinal-thalamo-cortical and frontoparietal pathways were associated with the patient’s headache severity and thermal pain sensitivity during the migraine attack. Migraineurs also had significantly lower variability and greater strength of dFC within the thalamo-cortical pathway (VPM-S1) than HCs. In contrast, migraine patients showed greater variability and lower strength of dFC within the frontoparietal pathway (dlPFC-IPC). Conclusions Migraine is associated with alterations in temporal signal variability in the ascending trigeminal somatosensory and top-down modulatory pathways, which may explain migraine-related pain and allodynia. Contrasting patterns of time-varying connectivity within the thalamo-cortical and frontoparietal pathways could be linked to abnormal network integrity and instability for pain transmission and modulation.